2000
DOI: 10.1017/s0022112099007582
|View full text |Cite
|
Sign up to set email alerts
|

Subgrid-scale interactions in a numerically simulated planar turbulent jet and implications for modelling

Abstract: The dynamics of subgrid-scale energy transfer in turbulence is investigated in a database of a planar turbulent jet at Reλ ≈ 110, obtained by direct numerical simulation. In agreement with analytical predictions (Kraichnan 1976), subgrid-scale energy transfer is found to arise from two effects: one involving non-local interactions between the resolved scales and disparate subgrid scales, the other involving local interactions between the resolved and subgrid scales near the cutoff. The former gives rise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 55 publications
6
52
0
Order By: Relevance
“…Spalart [2009] concluded his review of the state of the art in DES with four key future issues, the key theoretical component being the need to establish the link between a resolved DES flow field and the exact flow field in a similar fashion to a priori LES studies [Vreman et al, 1995;Akhavan et al, 2000]. Without such a connection, while DES represents a highly effective, practical tool, and research into optimal ways to represent environmental processes in DES is a sorely needed development, such enhancements will lack theoretical justification.…”
Section: Detached Eddy Simulation (Des)mentioning
confidence: 99%
“…Spalart [2009] concluded his review of the state of the art in DES with four key future issues, the key theoretical component being the need to establish the link between a resolved DES flow field and the exact flow field in a similar fashion to a priori LES studies [Vreman et al, 1995;Akhavan et al, 2000]. Without such a connection, while DES represents a highly effective, practical tool, and research into optimal ways to represent environmental processes in DES is a sorely needed development, such enhancements will lack theoretical justification.…”
Section: Detached Eddy Simulation (Des)mentioning
confidence: 99%
“…We have tried a mixed scale similarity model 24 , where the scale similarity model is combined with a dynamic eddy viscosity model. This model was tested for the channel flow simulations presented in this paper and it was found that the backscatter of the kinetic energy provided by the stochastic EASM is comparable to the prediction of this mixed scale similarity model.…”
Section: E Mean and Rms Of Sgs Dissipation And Forward And Backscattmentioning
confidence: 99%
“…The dynamic procedure proposed by Germano et al 18 for the Smagorinsky and eddy-diffusivity models 19 can predict backscatter of energy through a negative eddy viscosity and eddy diffusivity, but this causes numerical instabilities for realistic amounts of backscatter. Mixed models, which are based on a combination of the scale similarity model 20 and an eddy-viscosity or eddy-diffusivity model [21][22][23][24] , can in principle model backscatter of energy and a more intermittent SGS dissipation since the SGS stresses and scalar fluxes are less correlated with the strain-rate tensor and resolved scalar gradient, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In the perspective of developing a similarity mixed formulation [33][34][35][36][37][38][39][40] with correct near-wall scaling, a WALE formulation 16 for the eddy-viscosity term was recently proposed by Lodato et al:…”
Section: B Les Modeling Approachmentioning
confidence: 99%
“…Lodato et al, 19 in particular, used a discrete approximation with cutoff length-scale ∆ = 4/3∆ according to what was proposed by Akhavan et al, 33 this filter width being an optimal size in order to sufficiently isolate the smallest resolved scales. In the present study, a slightly higher-yet providing sufficient localization in physical space-value of 1.5∆ is adopted.…”
Section: 37mentioning
confidence: 99%